2007
DOI: 10.1074/jbc.m611206200
|View full text |Cite
|
Sign up to set email alerts
|

Group VIA Phospholipase A2 (iPLA2β) Participates in Angiotensin II-induced Transcriptional Up-regulation of Regulator of G-protein Signaling-2 in Vascular Smooth Muscle Cells

Abstract: Rgs2 (regulator of G-protein signaling-2)-deficient mice exhibit severe hypertension, and genetic variations of RGS2 occur in hypertensive patients. RGS2 mRNA up-regulation by angiotensin II (Ang II) in vascular smooth muscle cells (VSMC) is a potentially important negative feedback mechanism in blood pressure homeostasis, but how it occurs is unknown. Here we demonstrate that group VIA phospholipase A 2 (iPLA 2 ␤) plays a pivotal role in Ang II-induced RGS2 mRNA up-regulation in VSMC by three independent appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
67
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(70 citation statements)
references
References 69 publications
3
67
0
Order By: Relevance
“…In addition, we demonstrated that expressing iPLA 2 ␤ by adenovirus-mediated gene transfer in iPLA 2 ␤-null VSMC restored the ability of Ang II to increase RGS2 mRNA expression in a concentration-dependent manner (16).…”
mentioning
confidence: 79%
See 4 more Smart Citations
“…In addition, we demonstrated that expressing iPLA 2 ␤ by adenovirus-mediated gene transfer in iPLA 2 ␤-null VSMC restored the ability of Ang II to increase RGS2 mRNA expression in a concentration-dependent manner (16).…”
mentioning
confidence: 79%
“…The sequences of rat iPLA 2 ␤ antisense and sense oligodeoxynucleotides were previously described (16). The sequences of cAMP regulatory element (CRE)-decoy and mismatch controls were described by Park et al (23).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations